Adding the Team into T1 Translational Research: A Case Study of Multidisciplinary Team Science in the Evaluation of Biomarkers of Prostate Cancer Risk and Prognosis. (1st January 2019) - Marrone, Michael T; Joshu, Corinne E; Peskoe, Sarah B; De Marzo, Angelo M; Heaphy, Christopher M; Lupold, Shawn E; Meeker, Alan K; Platz, Elizabeth A
Abstract: BACKGROUND: Given translational research challenges, multidisciplinary team science is promoted to increase the likelihood of moving from discovery to health effect. We present a case study documenting the utility of multidisciplinary team science in prostate cancer tissue biomarker validation. METHODS: We used primary data generated by a team consisting of a pathologist, cancer biologists, a biostatistician, and epidemiologists. We examined their contributions by phase of biomarker evaluation to identify when, through the practice of team science, threats to internal validity were recognized and solved. Next, we quantified the extent of bias avoided in evaluating the association of Ki67 (immunohistochemistry), stromal cell telomere length (fluorescence in situ hybridization), and microRNA (miRNA) (miR-21, miR-141, miR-221; quantitative RT-PCR) with prostate cancer risk or recurrence in nested case–control studies. RESULTS: Threats to validity were tissue storage time (Ki67, miRNA) and laboratory equipment maintenance (telomeres). Solutions were all in the data analysis phase and involved using tissue storage-time specific cutpoints and/or batch-specific cutpoints. Bias in the regression coefficient for quantiles of each biomarker ranged from 24% to 423%, and the coefficient for the test for trend ranged from 15% to 910%. The interpretation of the associations changed as follows: Ki67, null to positive; stromal cell telomere length, null to positive; miR-21 and miR-141 remained null; miR-221, weak to moderate inverse. CONCLUSIONS: In this case study, we documented the inferential benefits of multidisciplinary team science when the team's collaboration and coordination led to the identification of threats to validity and the implementation of appropriate solutions.